CHALLENGES IN IMPLEMENTING PROBLEM BASED LEARNING IN MADRASAH ALIYAH - Suyuti Suyuti (Adisam Publisher, 2025)
PBL is a learning method that is focused on solving real problems, which aims to improve students' analytical, critical and collaborative skills. Despite having various benefits, implementing PBL in Madrasah Aliyah faces a number of significant challenges. One of the main challenges is limited resources, including facilities, supporting tools, technology and funds. Teacher readiness is also a crucial obstacle, because not all teachers have sufficient knowledge and skills to implement PBL effectively. The school mentality and culture that is still attached to traditional learning methods also makes the transition process to PBL difficult. Time management was another challenge, given the busy curriculum and difficulty in managing time for PBL projects. In addition, evaluating and assessing student learning outcomes in a PBL context requires the development of more adaptive and relevant tools. The final challenge is in terms of collaboration and engagement, both between students and with external parties such as the community and industry. This research concludes that to overcome these challenges, commitment and collaborative efforts are needed from various parties, including school management, teachers, students, parents and other stakeholders. Potentially effective solutions include intensive training for teachers, development of supportive policies, and the formation of strategic partnerships with external parties. In this way, obstacles in implementing PBL can be overcome and this method can provide maximum benefits in improving the quality of education at Madrasah Aliyah.